Exploring basin scale salinity problems using a simplified water accounting model: the example of Zayandeh Rud Basin, Iran - Droogers, Peter; Salemi, H.R.; Mamanpoush, A.R. (Wiley, 2001)
Water scarcity and salinization are major threats to sustainable irrigation in Iran as well as other parts of the world. Irrigation schemes are part of a basin and as such, irrigation research must be conducted in a basin context. For the Zayandeh Rud basin in central Iran, a simplified water and salinity basin model (WSBM) was developed for a quick analysis of river basin processes. First the model was calibrated and used for current and past water resources analyses. Despite the simplicity of the model, observed and simulated streamflows were similar, proving that the model could be used for scenario analyses. The first senario was set up to analyze the effect of more efficient irrigation techniques on the basin water resources, where it was assumed that farmers would never accept lower water allocations if they invest in these more efficient techniques. As a consequence of this, return flows will decrease, resulting in less water available for downstream users. It was concluded that the effect on the downstream irrigation schemes was dramatic, with a 22% decrease in yield. Obviously, upstream yields will increase. A second scenario was defined where the effect of an increase of water extraction for the town of Esfahan was evaluated. In terms of basin-scale water quantity aspects this increased extraction is negligible as extractions are relatively low and return flows are high. The last scenario was developed to study the additional releases required from the reservoir to provide sufficient water for expansion of the tail-end Rudasht irrigation scheme. If no restriction is imposed on water quality, additional releases from the reservoir are limited. However, if salinity levels are not to exceed 2 dS m-1, mean annual water release requirements from the reservoir will increase from 52 to 64 m3 s-1, and peak requirements during the irrigation season will increase from 85 to 112 m3 s-1. Finally, it was concluded that the methodology and the model developed were useful for a swift and transparent analysis of past, current and future water and salt resources, and to perform scenario analyses.